Health-related fitness benefits following concurrent high-intensity interval training and resistance training in patients with type-1 diabetes or type-2 diabetes - Scoubeau, Corentin; Klass, Malgorzata; Celie, Bert; Godefroid, Chantal; Cnop, Miriam; Faoro, Vitalie (Frontiers in Physiology, 2024)
IntroductionCardiorespiratory fitness (CRF), as assessed by VO2peak, along with metabolic and cardiovascular health indices, represents the strongest predictors of survival. However, it remains unclear whether concurrent high-intensity interval training (HIIT) and resistance training (RT) can similarly enhance these health markers in patients with type-1 diabetes (T1D) or type-2 diabetes (T2D) compared to healthy individuals.MethodsAdults with uncomplicated T1D or T2D and healthy normoglycemic controls matched for sex and age (HC1 and HC2) performed 3 training sessions/week of concurrent HIIT and RT for 12 weeks. Pre- and post-intervention assessments included: lipids and glycemic profile, body composition (dual-energy x-ray absorptiometry) and a cyclo-ergometric cardio-pulmonary exercise test.ResultsTraining improved VO2peak, the ventilatory threshold (VT1), maximal workload, ventilation and O2pulse, similarly in T1D in HC1 without changes in body composition or glycemic profile. In patients with T2D, training improved insulin sensitivity (HOMA-IR), lean mass, VE/VCO2 slope, VT1 and maximal O2pulse, workload and VO2peak with reduction in fat mass and visceral adipose tissue (VAT) (all, p < 0.05). However, improvements in VO2peak and O2pulse were lower than in healthy controls (respectively, T2D: +9%, HC2: +18% and T2D: +6%, HC2: +19%, p < 0.05).ConclusionsBoth patients with T1D and T2D benefit from combined HIIT and RT by improving CRF with specific adaptations influenced by the presence and type of diabetes. While identical magnitude of achievements were observed in T1D and HC1, T2D patients exhibited lower VO2peak and maximal O2pulse improvements but associated with notable additional health benefits regarding insulin sensitivity, body composition, visceral adipose tissue and ventilatory efficiency.